Physical Activity and Sedentary Behaviors Associated With Risk of Progression From Gestational Diabetes Mellitus to Type 2 Diabetes Mellitus: A Prospective Cohort Study - Bao, Wei (2014)
IMPORTANCE: Women with a history of gestational diabetes mellitus (GDM) are at substantially increased risk of type 2 diabetes mellitus (T2DM). The identification of important modifiable factors could help prevent T2DM in this high-risk population. OBJECTIVE: To examine the role of physical activity and television watching and other sedentary behaviors, and changes in these behaviors in the progression from GDM to T2DM. DESIGN, SETTING, AND PARTICIPANTS: Prospective cohort study of 4554 women from the Nurses’ Health Study II who had a history of GDM, as part of the ongoing Diabetes & Women’s Health Study. These women were followed up from 1991 to 2007. EXPOSURES: Physical activity and television watching and other sedentary behaviors were assessed in 1991, 1997, 2001, and 2005. MAIN OUTCOMES AND MEASURE: Incident T2DM identified through self-report and confirmed by supplemental questionnaires. RESULTS: We documented 635 incident T2DM cases during 59287 person-years of follow-up. Each 5–metabolic equivalent hours per week (MET-h/wk) increment of total physical activity, which is equivalent to 100 minutes per week of moderate-intensity physical activity, was related to a 9% lower risk of T2DM (adjusted relative risk [RR], 0.91; 95% CI, 0.88–0.94); this inverse association remained significant after additional adjustment for body mass index (BMI). Moreover, an increase in physical activity was associated with a lower risk of developing T2DM. Compared with women who maintained their total physical activity levels, women who increased their total physical activity levels by 7.5 MET-h/wk or more (equivalent to 150 minutes per week of moderate-intensity physical activity) had a 47% lower risk of T2DM (RR, 0.53; 95% CI, 0.38–0.75); the association remained significant after additional adjustment for BMI. The multivariable adjusted RRs (95% CIs) for T2DM associated with television watching of 0 to 5, 6 to 10, 11 to 20, and 20 or more hours per week were 1 (reference), 1.28 (1.04–1.59), 1.41 (1.11–1.79), and 1.77 (1.28–2.45), respectively (P value for trend <.001); additional adjustment for BMI attenuated the association. CONCLUSIONS AND RELEVANCE: Increasing physical activity may lower the risk of progression from GDM to T2DM. These findings suggest a hopeful message to women with a history of GDM, although they are at exceptionally high risk for T2DM, promoting an active lifestyle may lower the risk.